STEM Based Ecosystem Module: An Effort to Improve Students’ Science Process Skill - Thahara Sumayya Zulkarnain; Indayana Febriani Tanjung (Universitas Pendidikan Ganesha, 2023)
Students' mastery of science process skills is still low, as illustrated in several studies caused by the use of inappropriate learning methods so that students do not understand the skills of applying science processes optimally. Therefore, educators need to use an approach that is able to train the mastery of science process skills. One approach that applies scientific work principles is the STEM approach. The integration of the STEM approach in learning can support mastery of science process skills. This study aims to develop the STEM-based modules on ecosystem material in order to improve students' science process skills. The development research (R&D) method in this study uses 4D models. A module validity test is used to evaluate the developed module, which is measured using an instrument in the form of a validation questionnaire from media and material experts. Data analysis techniques use quantitative methods, namely calculating the percentage value of the Likert scale. The module is very valid, according to the testing of two expert validators, with sequential validity percentages of 97% and 98%. The results of the practicability test for educator and student responses are 81% and 93.71%, respectively, indicating that the module is very practical. The analysis of the effectiveness test of the module obtained an N-gain score of 0.76 with high criteria or it was said that science process skills increased. Thus, the developed STEM-based ecosystem module is valid, practical and effective, and makes it easy to understand ecosystem material, increases sensitivity to solving environmental problems and becomes an effort to improve students' science process skills.